LEGAL STRATEGY FOR EMPOWERING CUSTOMARY INSTITUTIONS THROUGH CUSTOMARY LAND REGISTRATION - Andi Tira; Zulkifli; Juliati; Adi Muliawansyah Malie (Faculty of Law, Universitas Pekalongan, 2025)
Customary institutions have an important position for indigenous peoples both as cultural symbols and as a means of controlling the lives of indigenous peoples so it is important to be legally protected. Customary institutions need legal certainty through normative recognition from the government. The purpose of this research is first, to analyze the existence of indigenous peoples through three indicators: (1) there is a customary law community (2) there is an area or customary land (3) there is a customary legal order. Second, to analyze the registration of customary land rights as a legal strategy to empower customary institutions. The type of research used is qualitative with a normative-empirical approach. The normative approach uses the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 14 of 2024 concerning the Implementation of Land Administration and Registration of Customary Land Rights of Customary Law Communities. While the empirical approach is through a survey of the existence of indigenous peoples. There are two types of data used, namely primary data obtained through interviews and secondary data obtained through the review of laws and regulations, journals and legal literature. The results showed that first, the existence of Patongloan customary law communities fulfills the indicators: (1) There is a group of people who have an attachment to hereditary traditions adhered to as guidelines for daily life including in dispute resolution, (2). There is a customary area occupied by the community to fulfill the needs of life together, called customary land. (3), There is a customary legal order inherited by the Patongloan community. Second, the strategic step to empower Patongloan customary institutions is through the registration of customary land rights at the Enrekang Regency Land Office. This study recommends that Patongloan customary institutions register their customary land in the form of management rights and/or as joint property rights.